2013
DOI: 10.2174/156652413804810727
|View full text |Cite
|
Sign up to set email alerts
|

PRAME/EZH2-Mediated Regulation of TRAIL: A New Target for Cancer Therapy

Abstract: The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exerts a cancer cell-specific pro-apoptotic activity. This property made the TRAIL associated pathway one of the most promising strategies aimed at inducing tumor-selective death. In fact, several approaches have been considered to explore this pathway for cancer therapy, such as recombinant TRAIL, agonist antibodies for TRAIL receptors, and adenoviral TRAIL. However, all of these approaches have certain disadvantages that limit their clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Although the function of PRAME in tumourigenesis has not yet been fully elucidated, it is known that PRAME can bind to the retinoic acid receptor in the presence of retinoic acid and thereby repress retinoic acid receptor signalling and TRAIL expression, causing cell proliferation and preventing apoptosis and cell‐cycle arrest . The function of NY‐ESO‐1 in tumourigenesis also remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the function of PRAME in tumourigenesis has not yet been fully elucidated, it is known that PRAME can bind to the retinoic acid receptor in the presence of retinoic acid and thereby repress retinoic acid receptor signalling and TRAIL expression, causing cell proliferation and preventing apoptosis and cell‐cycle arrest . The function of NY‐ESO‐1 in tumourigenesis also remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that use of systems biology and network modeling is revealing a vast new set of intracellular proteins that could be therapeutically targeted to increase TRAIL-induced apoptosis. Interestingly enough, TRAIL expression can be inhibited by PRAME/EZH2 complex in CML (chronic myeloid leukemia) patients, and restoration of TRAIL expression enhanced sensitivity to chemotherapeutic drugs (De Carvalho et al, 2011; De Carvalho et al, 2013). …”
Section: Resistance To Trail—mediated Cell Deathmentioning
confidence: 99%
“…Forth, TRAIL deficiency in mice was associated with increased carcinogen-induced tumorigenesis and metastasis, particularly to the liver (Cretney et al, 2002; Sedger et al, 2002). Fifth, TRAIL expression is down regulated in a variety of human cancers and restoration of TRAIL expression enhances in vitro tumor sensitivity to chemotherapeutic drugs (De Carvalho et al, 2011, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Because of the low sensitivity and high toxicity of chemotherapy drugs, the identification of a new treatment for gastric cancer is urgent. Recombinant TRAIL has been tested in clinical trials and has shown promising anti‐tumor activities with mild side effects . However, resistance to TRAIL is a major clinical challenge in gastric cancer cells, leading to the failure of treatment, poor prognosis, and reduced cancer patient survival .…”
Section: Discussionmentioning
confidence: 99%